(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Tolerance as a socio-political phenomenon originated from ancient times, it opened the world to the formation of a welfare society and a system of associated values, and strengthened such values as freedom, equality, respect for a person, for his person.